L’Espagne comme île orientale à la périphérie de l’Europe dans les descriptions du récit de voyage de Gautier - Benda, Mihály (Verbum – Analecta Neolatina, 2008)
Travelling in the Orient has been an old dream shared by many travellers since the beginning of the 18th century and a popular theme in philosophical and political writings. The Orient is a universe where life is radically different from that in the West. In the 19th century, exploring the Orient first helped one get to better know the other and satisfy a desire for the exotic. For a European of this era, the Orient was the tales of One Thousand and One Nights, full of fantastic lives and enchanted palaces. The travel to that wide romantic East, spreading from Spain to the Levant, was quite often at the origin of a sudden awareness and always an opportunity for a restatement for such writers as Lamartine, Nerval, Flaubert, or even Gautier and Chateaubriand.